2019
DOI: 10.1080/02656736.2019.1690168
|View full text |Cite
|
Sign up to set email alerts
|

The value of iterative metal artifact reduction algorithms during antenna positioning for CT-guided microwave ablation

Abstract: Objectives: To compare image quality between filtered back projection (FBP) and iterative reconstruction algorithm and dedicated metal artifact reduction (iMAR) algorithms during antenna positioning for computed tomography-guided microwave ablation (MWA). Materials and methods: An MWA antenna was positioned in the liver of five pigs under CT guidance. Different exposure settings (120kV p /200mAs-120kV p /50mAs) and image reconstruction techniques (FBP, iterative reconstruction with and without iMAR) were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Detailed analysis revealed that using iMAR with tin filtration led to slight artefact reduction in comparison to using a tin filter protocol without iMAR, and that using iMAR with a routine-dose protocol resulted in strong artefact reduction in comparison to a routine-dose protocol without iMAR. Previous studies (13,15,(19)(20)(21) have reported a reduction in metal artefacts from metal needles in CT-guided microwave ablation, metallic thoracic implants, hip prostheses, dental hardware, and spinal implants when iMAR is used, which is consistent with our results for metal needles in lung biopsy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Detailed analysis revealed that using iMAR with tin filtration led to slight artefact reduction in comparison to using a tin filter protocol without iMAR, and that using iMAR with a routine-dose protocol resulted in strong artefact reduction in comparison to a routine-dose protocol without iMAR. Previous studies (13,15,(19)(20)(21) have reported a reduction in metal artefacts from metal needles in CT-guided microwave ablation, metallic thoracic implants, hip prostheses, dental hardware, and spinal implants when iMAR is used, which is consistent with our results for metal needles in lung biopsy.…”
Section: Discussionsupporting
confidence: 92%
“…During a CT-guided biopsy, iMAR reconstruction can improve the display of lesions when metal artefacts significantly limit their visibility (15). Our results indicated that images obtained with the iMAR algorithm showed a significant decrease in the degree of artefacts compared to images without iMAR.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In further studies this effect is to be evaluated using algorithms for metal artifact reduction. 30,31 This also includes the dual-energy CT monitoring of cryoablation, whose application in a first study showed a better visualization of the cryoablation zone. 15 To achieve a better contrast-to-noise ratio, the energies should be optimized for the respective application.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the metal can be one of the reasons for the high standard deviation in the Bland‐Altman analysis. In further studies this effect is to be evaluated using algorithms for metal artifact reduction 30,31 . This also includes the dual‐energy CT monitoring of cryoablation, whose application in a first study showed a better visualization of the cryoablation zone 15 .…”
Section: Discussionmentioning
confidence: 99%